Recent Pharmacological Developments on Rhodanines and 2, 4-Thiazolidinediones. (2nd May 2013) - Bhatti, Ravinder Singh; Shah, Sakshi; Suresh,; Krishan, Pawan; Sandhu, Jagir S.
Abstract : Thiazolidines are five-member heterocyclic having sulfur, nitrogen, and oxygen atoms in their ring structure and exhibiting potent as well as wide range of pharmacological activities. In this minireview, recent updates on synthesis and pharmacological evaluations of molecules based on 2, 4-thiazolidine and rhodanine are discussed.